Konservasi Citrus spp. di Kebun Raya Bali serta Potensi Pemanfaatannya - I PUTU AGUS HENDRA WIBAWA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Citrus spp conservation. in Bali Botanical Gardens and Potential UtilizationCitrus is one of the genus on Rutaceae. Plants who derived from East Asia and Southeast Asia has many benefits because in addition to having fruits rich with vitamin C, also produces essential oils in some parts of the body. Essential oil is widely used in the field of food flavoring industry, comestics and perfumery industries. Essential oil is widely used for treatment as aromatherapy. In plant breeding efforts the existence of various wild species is important to ensure the availability of genes, so that efforts to improve the quality of the plant can still be done. Several factors such as pests and diseases can cause the presence of Citrus spp. threatened sustainability. Therefore, it is necessary to do a conservation effort to protect and preserve it. Bali Botanical Gardens as one of the ex-situ conservation agencies, is in charge of preserving various types of plants from nature. Until the Year 2017 Bali Botanical Garden has collected 12 types of Citrus among others; C. aurantifolia, C. aurantium, C. amblycarpa, C. hystrix, C. grandis, C. maxima, C. medica, C. natsudaidai, C nobilis, C nobilis var. microcarpa C. papaya and Citrus sp. which originated from several regions in Indonesia. Judging from its content, essential oil from Citrus spp. potentially exploited as anti-insect and anti-cancer.